Effectiveness of Early Versus Delayed Antibiotic Therapy in the Management of Sepsis in Adults: A Systematic Review - Dr. J. Arunkumar; Dr.G. Muthukavitha; Dr.R. Gopinath; Dr.R. Gopinath; Dr. R. Gopinathan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Sepsis is a life-threatening condition characterized by a dysregulated host response to infection, leading to organ dysfunction. Timely administration of antibiotics is considered crucial in its management. However, the optimal timing of antibiotic therapy remains a subject of ongoing debate. Objective: This systematic review aims to evaluate the current evidence on the effectiveness of early versus delayed antibiotic administration in reducing mortality and improving clinical outcomes in adult patients with sepsis. Methods: A systematic search of PubMed, Embase, Cochrane Library, and Scopus was conducted for studies published between January 2010 to December 2024. Randomized controlled trials (RCTs), cohort studies, and observational studies comparing early (within 1 hour of recognition) versus delayed antibiotic therapy (beyond 1 hour) in adult septic patients were included. Outcomes assessed included all-cause mortality, ICU length of stay, organ dysfunction, and time to hemodynamic stabilization. Results: Twenty-one studies (8 RCTs and 13 observational studies) were included. Early administration of antibiotics (within 1 hour) was associated with a significant reduction in 28-day mortality (RR: 0.74; 95% CI: 0.62–0.88). Delays beyond 3 hours showed a marked increase in mortality (RR: 1.35; 95% CI: 1.12–1.61). Early therapy was also linked with shorter ICU stays and faster reversal of septic shock. Conclusion: Early administration of antibiotics, particularly within the first hour of sepsis recognition, significantly improves survival outcomes and reduces complications. This review reinforces current guidelines advocating for prompt antibiotic delivery in suspected sepsis.